OPTIMAL CONTROL FOR A DISCRETE MODEL OF HEPATITIS C WITH LATENT, ACUTE AND CHRONIC STAGES IN THE PRESENCE OF TREATMENT. (2020) - YOUSSOUFI, LAHCEN EL; MOUTAMANNI, HAJAR; LABZAI, ABDERRAHIM; BALATIF, OMAR; RACHIK, MOSTAFA
No abstract available